A congestion control method based on loading-feedback in MTC - Hongguang DUAN; Songpin LU; Lifei WANG; Dan TAN; Jiangqi GAO (Dianxin kexue)
Through analyzing the access efficiency of machine type communication（MTC）devices in LTE-Advanced system,a loading-feedback control method was proposed.The current access load was estimated and the load of next access slot were calculated using the preamble state information,and the access control parameters for MTC device were adjusted based on the load change dynamically.The good performance of the proposed solution was evaluated by computer simulations.The simulation result shows that the proposed scheme can reduce the impact of nearly simultaneous access of a large number of MTC devices on human-to-human（H2H）devices,decrease the number of retransmissions and improve the access success rate effectively.